Anestesia de jundiás cinzas e albinos em banho de imersão com metanosulfonato de tricaína ou propofol - Gressler, Luciane Tourem (2011)
The efficacy of immersion anaesthesia with tricaine methanesulfonate or propofol on silver catfish Rhamdia quelen was assessed through induction and recovery times and observation of mortality. Two types of comparisons were conducted: one contrasting grey silver catfish of three size ranges and another comparing two strains of the species, albino and grey. For tricaine methanesulfonate, there was no uniform relationship between the induction and recovery times and the size of the grey silver catfish. The grey animals were more sensitive to the anaesthetic than the albinos were, and recovery was also faster in the grey fish group. Induction of propofol anaesthesia had a direct relationship with size, with the small animals reaching anaesthesia stage earlier. No uniform pattern was observed for recovery among the three different sizes. Propofol promoted faster anaesthesia in the grey animals than in the albinos, but no direct relationship was observed for recovery between the strains. No mortality was detected throughout the experiment. This study reports a novel, efficient and practical use of propofol as an immersion anaesthetic for fish and notes the first time that silver catfish have been anesthetised with such an agent. The best outcomes with propofol were registered in the size range comparison, indicating that 12 mg.L-1 is the most efficient concentration to anesthetise the small fish and that 10 mg.L-1 is a more appropriate concentration for anaesthesia of the medium and large animals. With regard to tricaine methanesulfonate, 300 mg.L-1 promoted satisfactory results for anaesthesia of the large fish in the size range comparison and the albino in the strain comparison. The grey fish responded better to 100 mg.L-1 of the anaesthetic in the latter evaluation. These findings show that it is essential to consider size and strain when anesthetising silver catfish with tricaine methanesulfonate or propofol bath solution.